Antegrade balloon occlusion of inferior vena cava during thrombectomy for renal cell carcinoma - Metcalfe, Charles; Chang-Kit, Laura; Dumitru, Ioana; MacDonald, Shaun; Black, Peter (Canadian Urological Association Journal, 2013)
Nephrectomy with inferior vena cava (IVC) thrombectomy for advanced renal cell carcinoma (RCC) is a challenging and morbid surgical case. We describe the use of a simple endoluminal technique to occlude the suprahepatic IVC during thrombectomy. A 60-year-old male presented with a large right-sided RCC and IVC tumour thrombus. The tip of the thrombus, which was nonadherent to the caval wall, extended to the level of the hepatic veins. After complete dissection of the kidney, we obtained suprahepatic control of the IVC by a large compliant balloon, introduced through the right internal jugular vein and inflated just below the level of the diaphragm. The IVC thrombectomy was performed in a bloodless field. Mean blood pressure remained stable during IVC balloon inflation with a total occlusion time of 10 minutes. Intraprocedural completion cavogram and postoperative Doppler ultrasonography showed no residual IVC clot. Blood loss during the thrombectomy portion of the case was scant. The patient’s postoperative course was uncomplicated and, at the last followup, he had stable metastatic disease on sunitinib therapy. For the surgical treatment of RCC with retrohepatic IVC tumour extension, transjugular balloon occlusion of the suprahepatic IVC offers an alternative to extensive hepatic mobilization to obtain suprahepatic thrombus control. Advantages over traditional surgical methods may include decreased surgical time, lower risk of liver injury and tumour embolism. We suggest this method for further evaluation.